2015
DOI: 10.25100/cm.v46i3.1925
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonato de sodio versus solución salina isotónica para la prevención de la nefropatía inducida por medio de contraste: Revisión sistemática y meta-análisis

Abstract: Introduction: Contrast-induced nephropathy is one of the main causes of acute kidney injury and increased hospital-acquired morbidity and mortality. The use of sodium bicarbonate for nephroprotection has emerged as a preventative strategy; however, its efficacy is controversial compared to other strategies, such as hydration using 0.9% saline solution. Objective: To compare the effectiveness of sodium bicarbonate vs. hydration using 0.9% saline solution to prevent contrast-induced acute kidney injury. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…21 Sodium bicarbonate may have additional therapeutic benefits, including urinary alkalisation and free radical scavenging, but a meta-analysis of 5686 patients showed no clinical benefit of sodium bicarbonate over sodium chloride. 22 We are not aware of any trial that has compared giving a balanced crystalloid fluid with isotonic saline or isotonic sodium bicarbonate, despite the proved benefits of these fluids in other settings.…”
Section: Contrast Agentmentioning
confidence: 99%
“…21 Sodium bicarbonate may have additional therapeutic benefits, including urinary alkalisation and free radical scavenging, but a meta-analysis of 5686 patients showed no clinical benefit of sodium bicarbonate over sodium chloride. 22 We are not aware of any trial that has compared giving a balanced crystalloid fluid with isotonic saline or isotonic sodium bicarbonate, despite the proved benefits of these fluids in other settings.…”
Section: Contrast Agentmentioning
confidence: 99%
“…In patients with chronic kidney disease, it was shown that combined sodium bicarbonate and ascorbic acid administration could prevent CIN after catheterization [10]. However, a meta-analysis comparing sodium bicarbonate to 0.9% saline found that sodium bicarbonate did not reduce the risk of developing CIN [11]. And, while hydration with normal saline has been used as a prevention strategy, few studies have evaluated behavioral modifications of operators in the catheterization laboratory prior to procedures.…”
Section: Introductionmentioning
confidence: 99%
“…76 Finally, large-scale studies consistently fail to find a benefit of sodium bicarbonate over sodium chloride prophylaxis with respect to adverse post-contrast outcomes. 164,165 In short, the AMACING trial results showed that doing nothing was non-inferior to administering intravenous sodium chloride in the bulk of patients, and the current results cannot give direct insight into efficacy of sodium bicarbonate prophylaxis.…”
Section: Other Settingsmentioning
confidence: 78%
“…Whereas the recommendation of intravenous hydration as prophylaxis is found in most guidelines, specific protocols vary across guidelines and over time. 70,71,73,75,76,79,136 Taking together the facts that the AMACING trial found not giving prophylaxis to be non-inferior to prophylactic intravenous hydration with sodium chloride, and that large-scale studies find no benefit of sodium bicarbonate over sodium chloride, 164,165 it may well be possible that neither prophylactic strategy is effective at reducing the risk of post contrast adverse outcomes.…”
Section: Investigative Radiologymentioning
confidence: 99%
See 1 more Smart Citation